PEMAHAMAN DAN KEPEDULIAN GREEN ACCOUNTING PARA PELAKU UMKM INDUSTRI BATIK DI KECAMATAN ROGOJAMPI BANYUWANGI - Arvianti, Milfalia; Kartini, Titin; Herlindawati, Dwi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
This research aims to analyze the understanding and awareness of Green Accounting among MSMEs in the batik industry in Rogojampi District, Banyuwangi Regency. This research is a qualitative descriptive research. Data collection methods in this research were interviews, documents and observations. The data analysis method is carried out by reducing data, presenting data, and conclusions. The research results show that two of the three batik industries in Rogojampi District, Banyuwangi, have an understanding and concern for implementing Green Accounting. This is proven by environmental concern, awareness of environmental costs, knowledge of business costs, knowledge of environmental costs, apart from that it is proven by recording the costs of environmental activities. However, there is one industry that has not implemented Green Accounting as indicated by the absence of a waste processing site so that waste can cause public unrest. This happens because of the lack of knowledge of industry owners.